Reliability of maximal strength and peak rate of force development in a portable nordic hamstrings exercise device - Costa, J. A.; Spyrou, K.; Sancho, A.; Reis, J. F.; Brito, J. (Sensors, 2023)
The Nordic hamstring exercise (NHE) is a very popular exercise used to improve eccentric strength and prevent injuries. The aim of this investigation was to assess the reliability of a portable dynamometer that measures maximal strength (MS) and rate of force development (RFD) during the NHE. Seventeen physically active participants (34.8 ± 4.1 years; n = 2 women and n = 15 men) participated. Measurements occurred on two different days separated by 48-72 h. Test-retest reliability was calculated for bilateral MS and RFD. No significant test-retest differences were observed in NHE (test-retest [95% CI, confidence interval]) for MS [-19.2 N (-67.8; 29.4); p = 0.42] and RFD [-70.4 N·s-1 (-178.4; 37.8); p = 0.19]. MS showed high reliability (intraclass correlation coefficient [ICC] [95% CI], =0.93 [0.80-0.97] and large within-subject correlation between test and retest [r = 0.88 (0.68; 0.95)]. RFD displayed good reliability [ICC = 0.76 (0.35; 0.91)] and moderate within-subject correlation between test and retest [r = 0.63 (0.22; 0.85)]. Bilateral MS and RFD displayed a coefficient of variation of 3.4% and 4.6%, respectively, between tests. The standard error of measurement and the minimal detectable change for MS was 44.6 arbitrary units (a.u.) and 123.6 a.u., and 104.6 a.u. and 290.0 a.u. for peak RFD. This study shows that MS and RFD can be measured for NHE using a portable dynamometer. However, not all exercises are suitable to apply to determine RFD, so caution must be taken when analyzing RFD during NHE.